Turnover intention of nurses in public hospitals and its association with quality of working life: a cross-sectional survey in six provinces in China - Tang, Changmin; Zhou, Sitong; Liu, Chaojie; Min, Rui; Cai, Ruipeng; Lin, Taoyu (Frontiers in Public Health, 2023)
Objectives High turnover intention can exacerbate the workforce shortage of nurses. This study aimed to determine the level of turnover intention of public hospital nurses in China and its associated factors. Methods A cross-sectional questionnaire survey of 2,863 nurses was conducted in 48 public hospitals across six provinces in mainland China, measuring the sociodemographic (gender, age, marital status, and monthly basic salary) and work characteristics (professional title, workload, night sleep deprivation, and workplace violence) of respondents, their quality of working life (QWL), and turnover intention. Multivariate logistic regression models were established to determine the association between QWL and turnover intention after adjustment for variations of the sociodemographic and work characteristics. Results Overall, 42.8% of respondents reported turnover intention. Higher QWL scores (AOR = 0.824 for job and career satisfaction, p < 0.001; AOR = 0.894 for professional pride, p < 0.001; AOR = 0.911 for balance between work and family, p < 0.05) were associated with lower turnover intention. Workplace violence was the strongest predictor of higher turnover intention (AOR = 3.003–4.767) amongst the sociodemographic and work characteristics, followed by an age between 30 and 40 years (AOR = 1.457 relative to <30 years), and night sleep deprivation (AOR = 1.391–1.808). Senior professional title had a protective effect (AOR = 0.417 relative to no title) on turnover intention. Conclusion High levels of turnover intention are evident across China in nurses employed by public hospitals, in particular in those aged between 30 and 40 years. Low QWL and poor work environment are significant predictors of turnover intention.